The U.S. Supreme Court and racial minorities : two centuries of judicial review on trial - Goldstein, Leslie F. (Elgar studies in law and society, 2017)
The U.S. Supreme Court and Racial Minorities offers an in-depth, chronologically arranged look at the record of the U.S. Supreme Court on racial minorities over the course of its first two centuries. It does not pose the anachronistic standard, "Did the Supreme Court get it right?" but rather, "How did the Supreme Court compare to other branches of the federal government at the time?" Have these Justices, prevented against removal from office by discontented voters (in contrast to the President and the members of Congress), done any better than the elected branches of government at protecting racial minorities in America? Goldstein examines treatment of four racial minorities (Indians, Blacks, Asians, and Hispanics) in this investigation of the life-tenured Supreme Court's comparative willingness to protect racial minorities. She finds that judicial review, while no panacea, did help America's racial minorities: when the Court was willing to help, it was particularly willing to act to check state-level oppressive policies and federal-level administrative abuses. She also documents the Supreme Court's leadership role on the civil rights of Black Americans from 1911-1989. This book will be a critical resource not only for scholars of political science and law, but for anyone interested in the history of the treatment of racial minorities by the U.S. government and the value of judicial review as a protector of minority rights.